Teaching bioethics: models and contents. - Palazzani, Laura (Medicina e Morale, 1998)
The problem of teaching bioethics is extremely delicate and complex and it presents two kinds of difficulties, one regarding the "contents", and the other one regarding "principles". The difficulties regarding the contents are related to the fact that this subject is new and, consequently, to the lack of consolidated teaching models; whereas the theoretical difficultes are strictly related to the interdisciplinary characteristic (comparison and dialogue between various subjects) and to the theoretical and practical pluralism (plurality of moral and legal concepts) which is the peculiarity of bioethics. The author's question is: what bioethics teaching? And above all who, how, when, should bioethics be taught? But in particular who should teach bioethics? First of all one has to identify the students and distinguish between "general" teaching (and therefore for everyone) and "specific" teaching (for those who work in the social and health sector and to those who do not work directly or indirectly in the health service). On the other hand how to teach bioethics concerns three sectors: knowledge (detailed knowledge of scientific research and technology, applied to biology and to medicine, of the social and health structure, of theology and philosofy, knowing how to act and knowing how to be (it is important to know how to come down from the theoretical and cognitive level to the level of application and experience, both of acting and of being). The question of when to teach bioethics has not yet been solved. The question of who should teach bioethics is also still in experimentation: the best solution would be a team of professors of different but interacting subjects.